PEMBELAJARAN MENULIS TEKS EKSPLANASI DENGAN MODEL KOOPERATIF TIPE PICTURE AND PICTURE PADA SISWA KELAS XI SMK - Riska Nuryanti; Wikanengsih Wikanengsih; Deana San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Writing skills are generally regarded as difficult by students. In writing learning, many students have difficulty in pouring ideas into written language and not much vocabulary is mastered. This is based on the value of previous explanatory text writing skills getting an average value of 64.04 which certainly states that the students' ability in writing explanatory texts is still low. The formulation of the problem in this study is how the difficulties faced by students in writing explanatory texts learned in class XI. The purpose of this study is to improve students' ability to write explanatory texts using cooperative models of picture and picture types in the learning process. The method used by researchers is descriptive qualitative aims to describe what is learning to write explanatory texts by using a cooperative model of the type of picture and picture in class XI SMK students. This final result gets an average value of 80.13 which is the effectiveness of the application of the cooperative model of the picture and picture type in learning to write explanatory texts.